Does Social Media Content Affect Cash Waqf Literacy and Interest in Paying Cash Waqf Among Gen Z? - Sutisna, Fajar Andrian; Hilman Maulana Akbar; Nabiela Rizki Alifa (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
Waqf social institutions continue to promote waqf literacy through their social media accounts to ensure that the public, especially the younger generation, can understand and develop an interest in Waqf. This study aims to determine how much cash waqf literacy and the social media content of waqf institutions influence the interest in giving cash waqf among Generation Z in Indonesia. The research method was quantitative, with primary data from 201 respondents using purposive sampling. The data analysis model in this study employs the Structural Equation Model Partial Least Square (SEM-PLS). The results indicate that 73 individuals, or 36.3% of Generation Z, have engaged in cash waqf. The study also shows that cash waqf literacy and social media content each have a partial positive and significant impact on the interest in paying cash waqf among Generation Z. Furthermore, the variable of social media content has a positive and significant impact on the interest in giving cash waqf through cash waqf literacy among Generation Z. This research suggests that waqf institutions should enhance and improve their social media content to increase cash waqf literacy, which could further boost interest in cash waqf.